Resolution of macropinosomes, phagosomes and autolysosomes: Osmotically driven shrinkage enables tubulation and vesiculation. (21st September 2018) - Freeman, Spencer A.; Grinstein, Sergio
Abstract : Macropinosomes, phagosomes and autolysosomes are comparatively large, quasi‐spherical organelles that play essential functions in immunity and homeostasis. These vacuolar organelles are relatively short‐lived, promptly fragmenting into smaller structures. Vacuolar resolution is mediated by tubulation and vesiculation, processes orchestrated by protein complexes that are recruited to highly curved membranes. Importantly, the surface‐to‐volume ratios of the tubules and vesicles generated during the resolution process are considerably larger than that of the parental vacuole. Because membranes under high hydrostatic tension resist deformation, an active, concomitant loss of volume is required to sustain the resolution process and may even initiate tubulation and vesiculation. Despite its fundamental role in membrane remodeling, the mechanisms that account for organellar volume loss are poorly understood, but are likely to involve the export of solutes followed by osmotically obliged water. In this review, we describe the principles and possible mechanisms underlying the resolution of organelles, with particular attention paid to the osmolytes they contain and the pathways mediating their exit. Abstract : Traffic between intracellular organelles involves tubulation and vesiculation. These changes entail marked alterations in the surface to volume ratio of the organelle, requiring concomitant loss of luminal volume. We discuss the mechanisms, regulation and significance of the pathways that mediate the loss of solutes and water that enable organellar remodeling and traffic.